Can vague brand slogans promote desirable consumer responses?. Issue 4 (18th August 2014) - Strutton, David; Roswinanto, Widyarso
Abstract : Purpose: – This study aims to investigate the effects associated with the strategic use of vague, as opposed to precise, advertised brand slogans on various consumer responses. Design/methodology/approach: – A content analysis study was conducted to explore the pattern of vagueness in advertising slogans from 1, 441 consumer-oriented brands. Based on the resultant delineation/definition of vagueness, two experimental studies followed. Vignette advertising slogans were manipulated to achieve different level of vagueness. The initial 2 × 2 factorial between subjects design engaged vagueness level of brand slogans and consumers' need for cognition as factors. Brand recall functioned as the dependent variable. The second experiment featured another 2 × 2 factorial design that used vagueness level and length of brand slogan as factors. Brand attitude, persuasiveness and purchase intention functioned as dependent variables. Findings: – Vagueness level of advertising/branding slogans did not significantly affect brand recall. Interactions between vagueness level and length of advertisement slogans exercised significant effects on evoked thought, brand attitude and persuasiveness but not on purchase intention. At net, this study generated original theoretical and managerial insights about how and why desirable branding outcomes can be generated by managing the vagueness and word count of brand slogans, and a platform from which future research on this topic could be based. Research limitations/implications: – First, the sample was limited to the southwestern USA. Second, in the slogan vignettes that were used, other cues were deliberately eliminated. A brand slogan essentially devoid of other cues may have been perceived as less realistic by respondents, thus reducing the relevance of their responses. However, a similar tradeoff always exists between more realistic states and controlled conditions. Practical implications: – This study produces original theoretical and managerial insights about how and why several desirable branding outcomes are likely to result when vague, rather than precise, advertising slogans are deployed under certain manageable conditions. Each insight just referenced ensues from a study that itself was grounded in an extensive content analysis of contemporary print advertising slogans. This content analysis generated a substantial amount of practical and actionable insight about the treatment and use and management of slogans. This study demonstrates that the vagueness, precision and/or word count of slogans can be manipulated in ways that yield three communication outcomes that redound directly to the marketing interests of brand and advertising managers. Originality/value: – The findings provide unique insight into how vagueness level of advertising slogans can be managed and how such a level can affect consumers' perceptions.